Efficient Schottky Junction Construction in Metal‐Organic Frameworks for Boosting H2 Production Activity. Issue 13 (7th May 2021) - Wang, Yang; Zhang, Wei; Li, Dan; Guo, Jianping; Yu, Yu; Ding, Kejian; Duan, Wubiao; Li, Xiyou; Liu, Heyuan; Su, Pengkun; Liu, Bo; Li, Jianfeng
Abstract: Manipulation of the co‐catalyst plays a vital role in charge separation and reactant activation to enhance the activity of metal‐organic framework‐based photocatalysts. However, clarifying and controlling co‐catalyst related charge transfer process and parameters are still challenging. Herein, three parameters are proposed, V transfer (the electron transfer rate from MOF to co‐catalyst), D transfer (the electron transfer distance from MOF to co‐catalyst), and V consume (the electron consume rate from co‐catalyst to the reactant), related to Pt on UiO‐66‐NH2 in a photocatalytic process. These parameters can be controlled by rational manipulation of the co‐catalyst via three steps: i) Compositional design by partial substitution of Pt with Pd to form PtPd alloy, ii) location control by encapsulating the PtPd alloy into UiO‐66‐NH2 crystals, and iii) facet selection by exposing the encapsulated PtPd alloy (100) facets. As revealed by ultrafast transient absorption spectroscopy and first‐principles simulations, the new Schottky junction (PtPd (100)@UiO‐66‐NH2 ) with higher V transfer and V consume exhibits enhanced electron‐hole separation and H2 O activation than the traditional Pt/UiO‐66‐NH2 junction, thereby leading to a significant enhancement in the photoactivity. Abstract : An efficient Schottky junction PtPd cubes@UiO‐66‐NH2 is constructed by optimizing the V transfer, D transfer, and V consume, respectively. When compared to pristine UiO‐66‐NH2 and the traditional Schottky junction (Pt/UiO‐66‐NH2 ), PtPd cubes@UiO‐66‐NH2 with high V consume and V transfer show a >116‐ and 4.4‐fold enhancement in H2 generation, respectively.